Biomass production and management practices in mixed crop-livestock systems in the west African Sahel: Opportunities and constraints - Ouédraogo, I.; Ayantunde, Augustine A. (International Livestock Research Institute, 2019)
The Sahel is characterized by a marked inter-annual climate variability and has experienced a number of food security crises following the severe droughts during the 1970s and 1980s. Due to recent challenges such as rapid population growth, climate change, environmental concerns and market changes which cause major impacts to their production systems, the sahelian people have been shifting and adapting their production systems and the way they live to cope with uncertainties. The objective of the present report is to review the various biomass production and management issues in the mixed crop-livestock systems in West African Sahel. An elaborated literature survey of peer reviewed papers mostly, was conducted. The studies were based on the Sahel scale research, more specifically research that had been published on the West African Sahel, including studies published between 1990s and 2016. Results show that many factors have contributed to the changes, among which, rainfall variability, population growth, human induced-activities, land tenure systems and the effects of globalization. Various biomass production and management practices are employed in West African Sahel for both on-farm and off-farm biomass improvements. Some of the best practices are mulching, soil and water conservation techniques, composting, farmer managed natural regeneration, agroforestry, etc. These practices have overall contributed to increase agricultural productivity, ecosystem services provisioning and have sometime deepened the difference between men and women, rich and poor, young and old people. Most of the constraints associated with large adoption of the best practices in the Sahel are land tenure systems, the huge gap between inputs and output investment costs but, the climate conventions are offering new opportunities that will ultimately contribute to positive changes. This will be possible only when land tenure systems in the region are reinforced, institutional linkages are strengthened, and new information systems are used to inform farmers on climate issues and new agricultural practices.